You are on page 1of 9

Chapter 17 Indefinite Integral and Its Applications 115

CHAPTER 17 13.
∫x
2

( x 2 + 4)dx = ( x 4 + 4 x 2 )dx
1 5 4 3
Exercise 17A (p.177) = x + x +C
5 3

∫ 2 x dx = 2 4 x
1 3 11 4 1
+ C = x4 + C
∫ ( x + 3) ∫
1. 3 1
8 14. xdx = ( x 2 + 3 x 2 )dx
2 25 3
= x + 2x 2 + C

dx 1
2. = x+C 5
3 3

3. ∫
dx
= ∫ x −4 dx =
x −3 1
+ C = − x −3 + C
15. ∫ 4 cos xdx = 4 sin x + C
x4 −3 3
2 16. ∫ 8 sin xdx = −8 cos x + C
∫ ∫
3dx − 13 x3 9 2
4. 3 x
= 3 x dx = 3( 2
)+C = x3 +C
2
∫ (sin x + cos x )dx = − cos x + sin x + C
3
17.
2.2
∫ 3x
x 15
5. 1.2
dx = 3( ) + C = x 2.2 + C
∫ (4 cos x − 3 sin x )dx = 4 sin x + 3 cos x + C
2.2 11 18.

x 0.6

2
6. 0.4 x −0.4 dx = 0.4( ) = x 0.6 + C
0.6 3 19. ∫ (a cos x + b sin x )dx = a∫ cos xdx + b∫ sin xdx
= a sin x − b cos x + C
x3 x2
∫ (3 x − 2 x + 1)dx = 3( ) − 2( ) + x + C
2
7.
3 2
∫ 5 sec xdx = 5 tan x + C
2
20.
= x3 − x2 + x + C

x4 x2
∫ sin 2 x = ∫ csc
dx
∫ (2 x xdx = − cot x + C
2
8. 3
− 7 x + 6)dx = 2( ) − 7( ) + 6 x + C 21.
4 2
1 4 7 2
= x − x + 6x + C
∫ (3 ∫
2
)dx = (3 x 2 + 2 x − 2 )dx
1 1
2 2 22. x+
x
3 1
x6 x4 x2 x2 x2
∫ ( 4 x − 2 x + 9 x )dx = 4( ) − 2( ) + 9( ) + C = 3( ) + 2( )+C
9. 5 3
3 1
6 4 2 2 2
2 6 1 4 9 2 3 1
= x − x + x +C = 2x 2 + 4x 2 + C
3 2 2

∫ (4 x ∫
3
∫ ( x + 2)( x − 3)dx = ∫ ( x
2 2 1
10. 2
− x − 6)dx 23. 3
+ − 13
)dx = ( 4 x 3 + 3 x 3 )dx
x
1 1 5 4
= x3 − x2 − 6x + C x3 x3
3 2 = 4( 5
) + 3( 4
)+C
3 3
12 53 9 43
11. ∫ ∫
(2 x + 4)(3 x − 8)dx = (6 x 2 − 4 x − 32)dx =
5
x + x +C
4
x3 x2
= 6( ) − 4( ) − 32 x + C
3 2 3x 2 + 2 x − 1
∫ ∫
dx = (3 x 2 + 2 x 2 − x − 2 )dx
3 1 1
24.
= 2 x 3 − 2 x 2 − 32 x + C x
5 3 1
x2 x2 x2
= 3( ) + 2( )− +C
∫ (x ∫
+ 3 x − 5) x 3 dx = ( x 5 + 3 x 4 − 5 x 3 )dx
2
12. 5 3 1
2 2 2
1 6 3 5 5 4 6 25 4 23
= x + x − x +C
1
= x + x − 2x 2 + C
6 5 4 5 3
116 Chapter 17 Indefinite Integral and Its Applications

2 x +1
∫ ( x 4 − 23 x )dx = ∫ ( x
1 1 −4 1 − 13 dy
25. − x )dx (b) From (a), 4 =
2 dx x x+ x
−3 2
x 1x 3
2 x +1
= − +C
−3 2 23 ∴ ∫ 4dy = ∫ x x+ x
dx
1 3 2
= − x −3 − x 3 + C 2 x +1
3 4
∫ x x+ x
dx = 4 x + x + C

∫ 2 sin 2 cos 2 dx = ∫ sin xdx = − cos x + C


x x
26.
Exercise 17B (p.183)
∫ ∫
x
27. 4 sin 2 dx = 2(1 − cos x )dx
2 dy
= 2( x − sin x ) + C 1. =2
dx
= 2 x − 2 sin x + C
y = 2x + C
Put (1, 1) into y = 2 x + C , C = −1
∫ 3 tan ∫
xdx = 3(sec 2 x − 1)dx
28. 2

= 3(tan x − x ) + C ∴ y = 2x − 1
= 3 tan x − 3 x + C
dy
29.
∫ ∫
(tan x + cot x )2 dx = (tan 2 x + 2 + cot 2 x )dx 2.
dx
= 8x − 1

= ∫ (sec 2 x + csc 2 x )dx ∫


y = (8 x − 1)dx = 4 x 2 − x + C
= tan x − cot x + C Put (−1, −1) into y = 4 x 2 − x + C ,
−1 = 4( −1)2 − ( −1) + C
30.
∫ (sec x + tan x ) tan xdx C = −6


= (sec x tan x + tan 2 x )dx ∴ y = 4x2 − x − 6

= ∫ (sec x tan x + sec 2 x − 1)dx


dy
= sec x + tan x − x + C 3. = 4x + 1
dx

31. (a)
dy 2(1 − x 2 ) − 2 x ( −2 x )
= =
2 + 2x2 ∫
y = ( 4 x + 1)dx
dx (1 − x )
2 2
(1 − x 2 )2 = 2x2 + x + C
2 + 2x2 Put (−1, 3) into y = 2 x 2 + x + C , C = 2
(b) From (a), ∫ (1 − x 2 )2 ∫
dx = dy = y + C
Hence the equation of the curve is y = 2 x 2 + x + 2 .
2
∫ (1 − x 2 )2 + ∫ (1 − x 2 )2 ]
dx x dx
∴ 2[
dy d2y
4. If = kx + 3, =k
2 + 2x 2
dx 2
∫ (1 − x 2 )2 dx
dx
=
d2y
2x Q =2
= +C dx 2
1 − x2
∴ k=2
dy
32. (a)
dy 1 1 1
= ( x + x ) − 2 (1 + x − 2 )
1
= 2x + 3
dx 2 2 dx

=
1+ 1
2 x ∫
y = (2 x + 3)dx

2 x+ x = x 2 + 3x + C
2 x +1 Put (0, 4) into y = x 2 + 3 x + C , C = 4
=
4 x x+ x Hence the equation of the curve is y = x 2 + 3 x + 4 .
Chapter 17 Indefinite Integral and Its Applications 117

dy 1 3 1 2
5. Since = tan x sec x , Put (2, 5) into y = x − x − x + C2 ,
dx 6 2


y = (tan x sec x )dx 5=
8
6
− 2 − 2 + C2
= sec x + C 2
C2 = 7
Put (0, 1) into y = sec x + C , C = 0 3
Hence the equation of the curve is y = sec x . Hence the equation of the curve is
1 1 2
y = x3 − x2 − x + 7 .
6 2 3
dy
6. Since = 3 x + cos x ,
dx
9. v = 2t + 1

y = (3 x + cos x )dx

s = (2t + 1)dt = t 2 + t + C
3
= x 2 + sin x + C
2 When t = 0 , s = 0 . ∴ C = 0
3
Put (0, 3) into y = x 2 + sin x + C , C = 3 s = t2 + t
2
Hence the equation of the curve is
3 10. v = 3 t + 2
y = x 2 + sin x + 3 .

3
2 s = (3 t + 2)dt = 2t 2 + 2t + C
When t = 0 , s = 5 . ∴ C = 5
d2y
=4
3
7. s = 2t 2 + 2t + 5
dx 2


dy
= 4 dx = 4 x + C1
dx 11. a = 6t 2 + 4t


dy
When x = 1 , = 2 . ∴ C1 = −2 v = (6t 2 + 4t )dt = 2t 3 + 2t 2 + C
dx
dy When t = 0 , v = 4 . ∴ C = 4
= 4x − 2
dx v = 2t 3 + 2t 2 + 4

y = ( 4 x − 2)dx
= 2 x 2 − 2 x + C2 12. a = 12t 2 + 6t
Put (1, 3) into y = 2 x 2 − 2 x + C2 , C2 = 3 ∫
v = (12t 2 + 6t )dt = 4t 3 + 3t 2 + C1
Hence the equation of the curve is When t = 0 , v = −3 . ∴ C1 = −3
y = 2x2 − 2x + 3.
v = 4t 3 + 3t 2 − 3


s = ( 4t 3 + 3t 2 − 3)dt = t 4 + t 3 − 3t + C2
d2y
8. = x −1 When t = 0 , s = 0 . ∴ C2 = 0
dx 2
s = t 4 + t 3 − 3t

dy 1
= ( x − 1)dx = x 2 − x + C1
dx 2
dy 13. v = 4t + 2
When x = 2 , = −1. ∴ C1 = −1

dy 1 2
dx

s = ( 4t + 2)dt = 2t 2 + 2t + C
∴ = x − x −1 Let s = 0 when t = 0 , then C = 0 .
dx 2
s = 2t 2 + 2t

1
y = ( x 2 − x − 1)dx
2 When t = 4 , s = 2( 4)2 + 2( 4) = 40
1 3 1 2 ∴ The distance that the particle moves in the
= x − x − x + C2
6 2 first four seconds is 40 .
118 Chapter 17 Indefinite Integral and Its Applications

14. v = 2t − 4 When s = 20 , 5t 2 = 20
t = 2 or −2 (rejected)

s = (2t − 4)dt
v = 10(2)
= t 2 − 4t + C = 20

When t = 0, s = 0 2 − 4(0) + C = C ∴ The velocity is 20 m / s .

(a) When t = 2 , s = (2)2 − 4(2) + C = −4 + C d


17. (a) ( x tan x ) = x sec 2 x + tan x
∴ Distance = C − ( −4 + C ) = 4 dx
(b) When t > 2 , v > 0 dy 1
(b) = x sec 2 x + tan x
When t = 5 , s = (5) − 4(5) + C = 5 + C
2 dx 2

∫ ∫
1
∴ Distance = 2( 4) + 5 + C − C = 13 dy = ( x sec 2 x + tan x )dx
2
1
∴ y = x tan x + C
15. a = 48t − 24 2
π

v = ( 48t − 24)dt Since the curve passes through ( , 1) ,
4
= 24t 2 − 24t + C1 1 π π
1 = ( ) tan( ) + C
When t = 0 , v = 6 . ∴ C1 = 6 2 4 4
π
v = 24t 2 − 24t + 6 C = 1−
8


Hence the equation of the curve is
(a) s = (24t − 24t + 6)dt
2
1 π
y = x tan x + 1 − .
= 8t 3 − 12t 2 + 6t + C2 2 8
When t = 0 , s = −3 . ∴ C2 = −3
s = 8t 3 − 12t 2 + 6t − 3 18. (a) v = 60t − 30t 2
Put v = 0 ,
(b) Put v = 0 into v = 24t 2 − 24t + 6 ,
60t − 30t 2 = 0
24t 2 − 24t + 6 = 0 t (2 − t ) = 0
4t 2 − 4t + 1 = 0 t = 0 or t = 2
(2t − 1)2 = 0 ∴ His travelling time is 2 hours.
1
t= (b) v = 60t − 30t 2
2
1
∴ The particle is stationary when t = . ∫
s = (60t − 30t 2 )dt
2 = 30t 2 − 10t 3 + C
When t = 0, s = 30(0)2 − 10(0)3 + C
16. a = 10
=C

v = 10 dt = 10t + C1 When t = 2 , s = 30(2)2 − 10(2)3 + C
= 40 + C
When t = 0 , v = 0
∴ The distance between town A and town
∴ C1 = 0 B is ( 40 + C − C ) km = 40 km .
Then v = 10t
(c) v = 60t − 30t 2

s = 10tdt = 5t + C2 2
= 30 − (30 − 60t + 30t 2 )
When t = 0 , s = 0 = 30 − 30(1 − t )2
∴ C2 = 0 Therefore, v reaches its maximum when t = 1 .
∴ The maximum velocity is 30 km / h .
Then s = 5t 2
Chapter 17 Indefinite Integral and Its Applications 119

19. (a) a = 8 − 15t 2


∫ (x
−2
4. + 2 x −3 + 3 x −4 ) dx

v = (8 − 15t 2 )dt = 8t − 5t 3 + C
=
x −1
+ 2(
x −2
) + 3(
x −3
)+C
When t = 0 , v = 24 . ∴ C = 24 −1 −2 −3
Put v = 0 , then −5t 3 + 8t + 24 = 0 = − x −1 − x −2 − x −3 + C

5t 3 − 8t − 24 = 0
(t − 2)(5t 2 + 10t + 12) = 0
∫ (x − x ) ∫
2 4
5. 2
dx = ( x 2 − 4 + )dx
t=2 x2
∴ It stops once when t = 2 . 1 4
= x3 − 4x − + C
3 x
(b) (i) v = −5t 3 − 8t + 24


s = ( −5t 3 + 8t + 24)dt
x 4 + 2x3 + 9
5 4
=− t + 4t 2 + 24t + C1
6.
∫ x 2 ∫
dx = ( x 2 + 2 x + 9 x −2 )dx
1
= x 3 + x 2 − 9 x −1 + C
4
5 3
= − t 4 + 4t 2 + 24t (Put C1 = 0 )
4
When t = 2 ,
∫ ∫x
7 8 158
5
s = − (2) 4 + 4(2)2 + 24(2) = 44 7. x x x dx = 8
dx = x +C
4 15
∴ Distance travelled is 44 m .
(ii) When t = 4 ,
∫ (x ∫
+ 3 x 3 − 5 x ) x −3 dx = ( x 2 + 3 − 5 x −2 )dx
5
8.
5
s = − ( 4) 4 + 4( 4)2 + 24( 4) 1 3
4 = x + 3 x + 5 x −1 + C
= −160 3
When 2 < t < 4 , v < 0
∴ Distance travelled = [2( 44) + 160] m
= 248 m
9. ∫ (3sin θ + 4 cos θ)dθ = −3 cos θ + 4 sin θ + C

∫ cot ∫
θ dθ = (csc 2 θ − 1) dθ
2
10.
Revision Exercise 17 (p.186)
= − cot θ − θ + C

∫ (x ∫
+ 2)2 dx = ( x 4 + 4 x 2 + 4)dx
2
1.
∫ (sec θ + csc 2 θ)dθ = tan θ − cot θ + C
2
1 5 4 3 11.
= x + x + 4x + C
5 3

1 − cos 2θ 1 − (1 − 2 sin 2 θ)
12. =
∫ ( x − a)( x − b)dx = ∫ [ x − ( a + b) x + ab]dx 1 + cos 2θ 1 + (2 cos 2 θ − 1)
2
2.
1 3 1 2 sin 2 θ
= x − ( a + b) x 2 + abx + C =
3 2 2 cos 2 θ
= tan 2 θ
= sec 2 θ − 1
3.
∫ (ax + b)( px + q) dx 1 − cos 2θ
∫ 1 + cos 2θ dθ = ∫ (sec θ − 1)dθ
2
= ∫ [apx 2 + (bp + aq ) x + bq] dx
1 1 = ∫ sec 2 θdθ − ∫ dθ
= apx 3 + (bp + aq ) x 2 + bqx + C
3 2 = tan θ − θ + C
120 Chapter 17 Indefinite Integral and Its Applications

θ θ dy
13. (a) sin 4 + cos 4 16. (a) = 2x3 − 3
4 4 dx
4θ θ θ θ
= (sin
4
+ 2 sin 2 cos 2 + cos 4 )
4 4 4

y = (2 x 3 − 3)dx

2 θ 2 θ x4
− 2 sin cos = − 3x + C
4 4 2
2 θ 2 θ 2 1 θ θ x4
= (sin + cos ) − (2 sin cos )2 Put (2, 2) into y = − 3x + C ,
4 4 2 4 4 2
1 2θ C=0
= 1 − sin
2 2 x4
θ Hence the equation of the curve is y = − 3x .
(b) cos θ = 1 − 2 sin 2 2
2 dy
1 1 1 2θ (b) = −5
cos θ = − sin dx
4 4 2 2
3 1 1 2θ 2 x 3 − 3 = −5
+ cos θ = 1 − sin x = −1
4 4 2 2
θ θ θ x4
Put x = −1 into y = − 3x ,
∫ ∫
1
(sin 4 + cos 4 )dθ = (1 − sin 2 )dθ 2
4 4 2 2
7
y=

3 1
= ( + cos θ)dθ 2
4 4
7
3 1
= θ + sin θ + C ∴ The coordinates of the point are ( −1, ).
4 4 2

14. y = cot 3 θ − 3 cot θ 17 − 18. No solutions are provided for the H.K.C.E.E.
questions because of the copyright reasons.
dy
= 3 cot 2 θ( − csc 2 θ) − 3( − csc 2 θ)
dθ dV
= −3 cot 4 θ − 3 cot 2 θ + 3 cot 2 θ + 3
19. (a) = 3t 2 + 2t
dt
= −3 cot 4 θ + 3

V = (3t 2 + 2t )dt = t 3 + t 2 + C


∫ (−3 cot θ + 3)dθ When t = 2 , V = 14
4

= y + C1 ∴ C = 14 − 2 3 − 2 2 = 2
= cot 3 θ − 3 cot θ + C 1 V = t3 + t2 + 2
(b) When t = 5 ,
∫ ∫
−3 cot 4 θdθ = cot 3 θ − 3 cot θ + C1 − 3 dθ
V = (5)3 + (5)2 + 2 = 152
∫ cot θdθ = −3 [cot θ + −3 cot θ − 3θ] + C
4 1 3
∴ The volume of the bubble is 152 cm 3 .
cot 3 θ
=− + cot θ + θ + C 20. (a) V1 = 40 − 10t
3
V2 = t 2 − 10t + 24
dy When t = 4 ,
15. = 8 − 4x
dx V1 = 40 − 10( 4) = 0

y = (8 − 4 x )dx V2 = ( 4)2 − 10( 4) + 24 = 0
= 8x − 2 x 2 + C ∴ When t = 4 , V1 = V2
= −2( x − 2) + C1

2
(b) When 0 ≤ t ≤ 4 , h = V1dt
Q −2( x − 2)2 ≤ 0
∴ ymax = C1 = 7 ∫
h = ( 40 − 10t )dt

y = −2( x − 2) + 7 = −2 x + 8 x − 1
2 2 = 40t − 5t 2 (constant = 0)
Hence the equation of the curve is When t = 4 , h = 40( 4) − 5( 4)2 = 80
y = −2 x 2 + 8 x − 1 . ∴ The height of the particle is 80 m .
Chapter 17 Indefinite Integral and Its Applications 121

(c) When t ≥ 4 , h = V2 dt ∫ (c) By (b), 1 + 2(2) + 3(2)2 + L + 10(2)9


1 − (10 + 1)210 + 10(2)10 +1

1 =
h = (t − 10t + 24)dt = t 3 − 5t 2 + 24t + C
2
3 (1 − 2)2
When t = 4 , V1 = V2 (from (a)), = 9 217


h = V2 dt

= ∫ V1dt Enrichment 17 (p.188)


= 80 (from (b)) x3
∴ C = 42
2 1. (a) ∫ f ( x )dx =
3
− cos x + C
3

d
When t = 5 , [ f ( x )dx ] = x 2 + sin x
dx
1 2 1
h = (5)3 − 5(5)2 + 24(5) + 42 = 79 (b)
d
f ( x ) = 2 x + cos x
3 3 3 dx
1
∴ The height of the particle is 79 m .
∫ [ dx f ( x )]dx = x
d
3
2
+ sin x + C
dV1
(d) Q = −10 ≠ 14
dt
dV d
∴ Here we only consider a = 2 = 2t − 10 . 2. (a) [ xf ( x )] = xf ' ( x ) + f ( x )
dt dx
When a = 14 , xf ' ( x ) =
d
[ xf ( x )] − f ( x )
2t − 10 = 14 dx

∫ ∫ ∫
d
t = 12 xf ' ( x )dx = [ xf ( x )] dx − f ( x ) dx
dx

21. (a) Sn ( x ) = 1 + 2 x + 3 x 2 + L + nx n −1 ∫
= xf ( x ) − f ( x ) dx

∫ Sn ( x )dx
d
∴ (b) sec 2 x = 2 sec x (sec x tan x ) = 2 sec 2 x tan x
dx
= ∫ (1 + 2 x + 3 x 2 + L + nx n −1 )dx x d
(c) x sec 2 x tan x = ( sec 2 x )
2x 2
3x 2
nx n 2 dx
=x+ + +L+ +C By (a),
2 3 n
= x + x2 + x3 + L + xn + C x d 1 d
( sec 2 x ) = [ ( x sec 2 x ) − sec 2 x ]
2 dx 2 dx
Let K = x + x 2 + x 3 + L + x n .................(1)

∫ 2 ( dx sec x )dx
x d
xK = x 2 + x 3 + x 4 + L + x n +1 ................(2) 2

(1) − (2), (1 − x ) K = x − x n +1
= [ ∫ ( x sec 2 x )dx − ∫ sec 2 xdx ]
1 d
x − x n +1 2 dx
If x ≠ 1 , K =
1− x

∫ x sec
2
x tan xdx
x (1 − x n )
∴ ∫ Sn ( x )dx =
1− x
+ C ...............(3)
=
1 1
x sec 2 x − tan x + C
2 2
(b) Differentiate (3) with respect to x,


d
Sn ( x )dx
dx Classwork 1 (p.175)
(1 − x )[1 − (n + 1) x n ] − ( x − x n +1 )( −1)
=
(1 − x )2 x2
(1 − x )(1 − nx n − x n ) + x (1 − x n )
1. ∫ ∫
4 xdx = 4 xdx = 4(
2
) + C = 2x2 + C
Sn ( x ) =
(1 − x )2 x3
∫ ∫
7
7 x 2 dx = 7 x 2 dx = 7( ) + C = x3 + C
1 − (n + 1) x + nx n +1
n 2.
= 3 3
(1 − x )2
122 Chapter 17 Indefinite Integral and Its Applications

3 Classwork 4 (p.180)
∫ ∫
1 x2 3
3. 15 xdx = 15 x 2 dx = 15( 3
) + C = 10 x 2 + C
dy 3
2 1. Since = 4x − x2 ,
dx 2

∫ (2 x ∫ ∫ ∫ ∫
3 2
4. 3
+ x 2 − 1)dx = 2 x 3 dx + x 2 dx − dx y = ( 4 x − x )dx
2
x4 x3 x2 3 x3
= 2( ) + − x+C = 4( ) − +C
4 3 2 2 3
1 1 1
= x 4 + x3 − x + C = 2x2 − x3 + C
2 3 2
1 3
Put the point (2, 5) into y = 2 x 2 − x +C,
∫ (4 ∫ ∫ ∫
1 1 2
5. x − 3 x + 2)dx = 4 x dx − x dx + 2 dx
2 3
1
3 4
5 = 2( 2 ) 2 − ( 2 ) 3 + C
x 2
x 3 2
= 4( 3
)− 4
+ 2x + C C =1
2 3
8 23 3 43 Hence the equation of the curve is
= x − x + 2x + C 1
3 4 y = − x3 + 2x2 + 1.
2

Classwork 2 (p.176)

1. ∫ 3 sin xdx = 3∫ sin xdx = −3 cos x + C 2.


d2y
= 2(1 − x )
dx 2
d dy
2. ∫ (3 sin x + 2 cos x )dx = 3∫ sin xdx + 2∫ cos xdx ( ) = 2(1 − x )
dx dx
= −3 cos x + 2 sin x + C

dy
= 2(1 − x )dx
dx

∫ ∫ x2
sin x
3. dx = sec x tan xdx = sec x + C = 2 x − 2( ) + C1
cos 2 x 2
= − x 2 + 2 x + C1
∫ 3 sin ∫
x 1
4. 2
( )dx = 3 (1 − cos x )dx
2 2 dy
At (1, 3), = 5 = −(1)2 + 2(1)
∫ ∫
3 3
= dx − cos xdx dx
2 2 ∴ C1 = 4
3 3
= x − sin x + C
2 2 dy
Then = −x2 + 2x + 4
dx

Classwork 3 (p.177)

y = ( − x 2 + 2 x + 4)dx
1
= − x 3 + x 2 + 4 x + C2
(a) f ' ( x ) = − x sin x + cos x 3
Since (1, 3) is on the curve,
(b) Using the result of (a), we obtain 1
3 = − (1)3 + (1)2 + 4(1) + C2
∫ (− x sin x + cos x ) dx = f ( x ) + C1 = x cos x + C1 C2 = −
3
5

∫ − x sin xdx + ∫ cos xdx = x cos x + C1


3

Hence the equation of the curve is
∫ x sin xdx = ∫ cos xdx − x cos x − C1 1
y = − x3 + x2 + 4x − .
5
= sin x + C2 − x cos x − C1 3 3
= sin x − x cos x + C
Chapter 17 Indefinite Integral and Its Applications 123

Classwork 5 (p.183) ∴ The maximum height


2
1. Suppose v m/s and s m are the velocity of the = [ 2( 2 ) 2 − ( 2 ) 3 ] m
particle and its displacement from O after 3
8
travelling t1 seconds. = m
3

v = 10 dt = 10t + C1 = 2.67 m (corr. to 2 d.p.)

When t = 0 , v = 2 8
(c) When t = 2 , s =
∴ C1 = 2 3
When t = 2.5 ,
∴ v = 10t + 2 2
s = 2(2.5)2 − (2.5)3

s = (10t + 2)dt
25
3
= 5t 2 + 2t + C2 =
12
When t = 0 , s = 0 ∴ The distance it travels from
∴ C2 = 0 t = 2 to t = 2.5
8 25
∴ s = 5t 2 + 2t =( − )m
3 12
∴ When t = t1 , s = 5t12 + 2t1 = 0.58 m (corr. to 2 d.p.)
∴ The displacement at time t1 is (5t12 + 2t1 ) m .

2. (a) Let s m be the distance of the stone from the


ground at time t seconds after projection.
ds
= v = 4t − 2t 2
dt


2 3
s = ( 4t − 2t 2 )dt = 2t 2 − t +C
3
When t = 0 , s = 0
∴ C=0
2 3
∴ s = 2t 2 −
t
3
∴ The distance at time t seconds after projection
2
is (2t 2 − t 3 ) m .
3

ds
(b) When = v = 0 , 4t − 2t 2 = 0
dt
t = 0 or 2
d 2s
= 4 − 4t
dt 2
d 2s
= 4 − 4( 0 ) = 4 > 0
dt 2 t = 0
d 2s
= 4 − 4(2) = −4 < 0
dt 2 t = 2
∴ s attains its maximum when t = 2 .